2023
DOI: 10.3390/ma16237455
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of ZrB2-Copper Matrix Composites Produced by Ball Milling and Spark Plasma Sintering

Iwona Sulima,
Grzegorz Boczkal

Abstract: Copper matrix composites with zirconium diboride (ZrB2) were synthesised by ball milling and consolidated by Spark Plasma Sintering (SPS). Characterisations of the ball-milled composite powders were performed by scanning electron microscopy (SEM), X-ray diffraction, and measurement of the particle size distribution. The effect of the sintering temperature (1123 K, 1173 K, and 1223 K) and pressure (20 MPa and 35 MPa) on the density, porosity, and Young’s modulus was investigated. The relationship between the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The mixed powders were then suppressed under a pressure of 300 MPa with a holding time of 20 s. A sample mold with a dimension size of 32 mm × 8 mm × 5 mm was used for suppressing. After suppressing, samples were sintered under vacuum conditions by hot-press sintering under 35 MPa at 860-890 • C for 2 h. According to the literature, ZrB 2 exhibits a high degree of consolidation when the temperature is above 850 • C [18]. The mixed powders were then suppressed under a pressure of 300 MPa with a holding time of 20 s. A sample mold with a dimension size of 32 mm × 8 mm × 5 mm was used for suppressing.…”
Section: Preparation Of Materials and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed powders were then suppressed under a pressure of 300 MPa with a holding time of 20 s. A sample mold with a dimension size of 32 mm × 8 mm × 5 mm was used for suppressing. After suppressing, samples were sintered under vacuum conditions by hot-press sintering under 35 MPa at 860-890 • C for 2 h. According to the literature, ZrB 2 exhibits a high degree of consolidation when the temperature is above 850 • C [18]. The mixed powders were then suppressed under a pressure of 300 MPa with a holding time of 20 s. A sample mold with a dimension size of 32 mm × 8 mm × 5 mm was used for suppressing.…”
Section: Preparation Of Materials and Samplesmentioning
confidence: 99%
“…Yakut et al [ 17 ] added ZrB 2 into spherical graphite cast iron to investigate the effect on its mechanical properties and came to the conclusion that samples with the addition of 0.455% ZrB 2 showed the highest hardness (243 HB) and compressive strength (1438 MPa). Sulima et al [ 18 ] studied ZrB 2 –copper matrix composites produced by ball milling and spark plasma sintering and found a strong decrease in the electrical conductivity of composites containing 5% and 10 wt.% ZrB 2 , as well as in those containing larger amounts, due to the partial diffusion of boron into the copper matrix, although the hardness and Young’s modules of the samples were significantly improved. Zhao et al [ 19 ] prepared ZrB 2 -SiC- reinforced copper matrix composite coatings by laser cladding and found that the microhardness of the composite was about 5.6 times that of the copper matrix.…”
Section: Introductionmentioning
confidence: 99%